2011
DOI: 10.1203/pdr.0b013e31822f2411
|View full text |Cite
|
Sign up to set email alerts
|

High Cord Blood Levels of the T-Helper 2-Associated Chemokines CCL17 and CCL22 Precede Allergy Development During the First 6 Years of Life

Abstract: Exposure to a strong T-helper 2 (Th2)-like environment during fetal development may promote allergy development. Increased cord blood (CB) levels of the Th2-associated chemokine CCL22 were associated with allergy development during the first 2 y of life. The aim of the present study was to determine whether CB Th1-and Th2-associated chemokine levels are associated with allergy development during the first 6 y of life, allowing assessment of respiratory allergic symptoms usually developing in this period. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 29 publications
9
62
3
3
Order By: Relevance
“…Our results demonstrated that CGS significantly reduced the expression levels of CCR4 mRNA. CCR4 has a key pathogenic role in inflammatory conditions in allergies and autoimmune diseases [56,57]. CCR4 exerts its immunomodulatory effects by modulating Th cell function, as well as reducing the induction of regulatory T cells and the elevation of the differentiation of Th17 cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that CGS significantly reduced the expression levels of CCR4 mRNA. CCR4 has a key pathogenic role in inflammatory conditions in allergies and autoimmune diseases [56,57]. CCR4 exerts its immunomodulatory effects by modulating Th cell function, as well as reducing the induction of regulatory T cells and the elevation of the differentiation of Th17 cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tissue injury, Tregs restrict the infiltration of inflammatory cells through secretion of immunosuppressive cytokines, which has been well reviewed elsewhere [9]. For example, Tregs directly induce anti-inflammatory macrophages, which contribute to tissue repair during the initiation, maintenance and resolution phases [12, 44-46]. Tregs produce high levels of IL-10, which act directly on fibroblasts [47].…”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%
“…Interestingly, different allergic symptoms may be related to different chemokines. Furthermore, an imbalance in circulating Th1-and Th2-associated chemokines may precede the onset of sensitization, eczema, and recurrent wheeze from birth [73,74]. Supplementation with specific probiotic strains [75] may be detected by the presence of strain in stool samples.…”
Section: Lactobacillus Reuteri and Chemokinesmentioning
confidence: 99%